Impacto de las Remesas Extranjeras en el Desarrollo Empresarial del cantón Paltas, durante el Periodo 2010-2011 - Saraguro Eras, Mónica del Rocío (2016)
During the nineties and late twentieth century, the Ecuador experienced a severe economic crisis, the same that caused the sucre was devalued to levels never before presented, causing its demise and the country adopted the dollar as new currency U.S.. Leading to increasing levels of poverty and destitution, significantly reducing their purchasing power, besides presenting a series of economic phenomena that contracted the national economy. Under this backdrop, much of Ecuadorians opted to offer its workforce abroad, because in some countries it reached higher levels of compensation that could be obtained in Ecuador, for this reason several countries in Europe and the United States, began to attract people to do jobs that citizens do not want to perform. In this context, the most remote of national development zones such as avocados Canton, was presented a considerable flow of migrants, the urban and especially rural areas, whose residents were most affected by the economic crisis, the Most of the migrant population of the canton was oriented towards Europe, specifically Spain and other European countries. According to data from surveys of households observe that the family has 1 72.00% abroad, and seeing a small percentage of 3.73% with more than 10 family members who have migrated, ie families have migrated , 13.07% is stated that most of the members who migrate are the brothers, a 76.53% of the investigated sample report that their families thought stay of 1-5 years, the country has the highest percentage destination is Spain with a 75.20%, 7 54.13% of the people who have left the country say they have done in order to improve the quality of life of which 70.40% of these people send money to relatives The amount varies between 100-300 dollars a month which is the amount that has the highest percentage with 40.15%, 36.60% of the people receiving this money is invested in the purchase of housing and only a small percentage of 3.27% is invested in the acquisition of shares, a higher percentage is 47.83% of the investment in the construction sector and a small percentage of 3.48% in industry. Considering that migration has contributed greatly to the economy of Canton Avocado. This research is not intended to achieve a comprehensive understanding of migration, but provide elements for helping people understand, rehearsing an economic analysis yet incomplete, and, from the communities of origin, as is the canton Avocados, seeks , on the other hand, an analysis of the phenomenon of migration and the impact of remittances in the canton of avocados, which is essential with respect to the contribution to the development of a society such as business